Efektivitas Penggunaan Pembelajaran Daring Edmodo Berbantuan Quizstar untuk Meningkatkan Hasil Belajar Mahasiswa - Wajong, Aaltje D.C; Ridwan, Ridwan; Sangi, Nontje (Attractive : Innovative Education Journal, 2020)
This article aims to determine the effectiveness of using Edmodo-based online learning with the help of Quizstar to improve student learning outcomes for electric lighting installations. The research method used quasi-experimental design. Observation sheets and documentary studies were analyzed in this study. The subject were 43 students that consist of experimental class 21 and the control class 22 students. The research was conducted in six meetings, each class, namely three times meetings. The results showed the value of t count <t table (3.501 <1.997). This means that Ho is rejected so that Ha is accepted or it can be said that online learning using quizstar assisted edmodo is more effective than learning blogs for students majoring in electrical engineering education for semester 3 in the electrical power installation course.. Key words: Edmodo, Quizstar, Edmodo-based Online Learning